Pengendalian Hayati di Kampung Organik Brenjonk Desa Penanggungan, Kecamatan Trawas, Kabupaten Mojokerto - Ardiansyah, Moch Syaddad (Maliki Interdisciplinary Journal, 2025)
Brenjonk Organic Village is a village area in Penanggungan Village, Trawas District, Mojokerto Regency, East Java Province that has successfully implemented an organic farming system. The Brenjonk organic community aims to meet the needs of healthy and safe food for every family and preserve the environment. As a community that implements organic farming, the Brenjonk Organic Community also carries out efforts to control plant pests (OPT) naturally. The use of biological control agents, such as natural predators (Ladybugs), parasitoids (Trichogramma sp) and microorganisms (PGPR and mycorrhizal fungi), strengthens efforts to develop an environmentally friendly farming system.